Inflation and inflation uncertainty in the Euro Area - Guglielmo Maria Caporale; Luca Onorante; Paolo Paesani (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper estimates a time-varying AR-GARCH model of inflation producing measures of inflation uncertainty for the euro area, and investigates the linkages between them in a VAR framework, also allowing for the possible impact of the policy regime change associated with the start of EMU in 1999. The main findings are as follows. Steady-state inflation and inflation uncertainty have declined steadily since the inception of EMU, whilst short-run uncertainty has increased, mainly owing to exogenous shocks. A sequential dummy procedure provides further evidence of a structural break coinciding with the introduction of the euro and resulting in lower long-run uncertainty. It also appears that the direction of causality has been reversed, and that in the euro period the Friedman-Ball link is empirically supported, implying that the ECB can achieve lower inflation uncertainty by lowering the inflation rate.
Keywords: E31; E52; C22; 330; inflation; inflation uncertainty; time-varying parameters; GARCH models; ECB; EMU; Inflationserwartung; Inflation; Risiko; Europäischer Währungsverbund; Zentralbank; VAR-Modell; ARCH-Modell; EU-Staaten